Peran Manajemen Pegadaian Syariah dalam Meningkatkan Inklusi Keuangan Masyarakat - Rohmatul Laily Al Faiqoh; Mugiyati Mugiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the role of Islamic Pawnshop Management (Pegadaian Syariah) in enhancing financial inclusion among society, particularly for the lower-middle class and micro, small, and medium enterprises (MSMEs). Pegadaian Syariah provides Sharia-compliant financing services through various products such as gold pawning (rahn emas), gold savings, and micro-financing. This research employs a descriptive qualitative approach with data collection techniques that include literature studies, documentation, interviews, and observations. The data were analyzed systematically through the stages of reduction, presentation, and conclusion drawing to understand the strategies and impacts of Islamic Pawnshop Management on financial inclusion. The findings indicate that the management of Pegadaian Syariah, which applies the principles of good corporate governance and the values of maqashid shariah, has successfully improved public financial access in a fair, transparent, and sustainable manner. Digital innovation has proven to expand service reach to rural areas and enhance efficiency and customer satisfaction. Therefore, the existence of Pegadaian Syariah not only functions as a financing institution but also serves as a strategic instrument in supporting financial inclusion goals aligned with the SDGs, particularly in poverty alleviation and reducing social inequality.